IMPACT OF SOCIO-ECONOMIC FACTORS ON WOMEN’S ENTREPRENEURIAL INTENSION: THE MODERATING ROLE OF SKILL DEVELOPMENT - Rana Sakandar Hayat; Sadia Hussain; Sumera Iqbal (International Journal of Contemporary Issues in Social Sciences, 2024)
Women's participation in the workforce not only helps to shift the prevailing attitudes and economic structures within a region, but also has a significant impact on the economic well-being of their families. By earning a wage, women can supplement their family's income, leading to an improved standard of living and better overall health outcomes. Therefore, this study aims to find the relationship between socio-economics factors and female’s entrepreneurial intension. Further, it also tries to investigate the moderating role of skill development between socio-economics factors with Women’s entrepreneurial intension in the context of female in southern Punjab Pakistan. This study collected the data with authentic and well-developed questionnaire. The sample size for the analysis consisted on the 230 participant and further used Smart PLS for data analysis. This study found that the women participating are essential for the development of overall society. The study revealed the crucial role played by women in contributing to household economy, as reflected by the income generated by them being comparable to that of male workers. This can be attributed to the significant drive exhibited by housewives to assist their husbands in easing the financial burden, along with the favourable opportunities presented by natural resources. While the skill development program positively and significantly enhance the chances of Women’s entrepreneurial intension.